2016
DOI: 10.1021/acs.jmedchem.5b01699
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning Antitubercular 6-Nitro-2,3-dihydroimidazo[2,1-b][1,3]oxazoles for Neglected Tropical Diseases: Structure–Activity Studies on a Preclinical Candidate for Visceral Leishmaniasis

Abstract: Phenotypic screening of representative examples against kinetoplastid diseases unexpectedly led to the identification of DNDI-VL-2098 as a potential first-in-class drug candidate for visceral leishmaniasis (VL). Additional work was then conducted to delineate its essential structural features, aiming to improve solubility and safety without compromising activity against VL. While the 4-nitroimidazole portion was specifically required, several modifications to the aryloxy side chain were well tolerated e.g., ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(114 citation statements)
references
References 62 publications
(209 reference statements)
4
110
0
Order By: Relevance
“…Here, new synthesis was directed at the optimisation of solubility, efficacy, and safety, primarily through the incorporation of heterocycles to reduce compound lipophilicity 11 (estimated by CLogP data derived from ACD LogP/LogD software, version 12.0; Advanced Chemistry Development Inc., Toronto, Canada). Kinetic aqueous solubility measurements were conducted on dry powder forms of particular examples that were being considered for further evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, new synthesis was directed at the optimisation of solubility, efficacy, and safety, primarily through the incorporation of heterocycles to reduce compound lipophilicity 11 (estimated by CLogP data derived from ACD LogP/LogD software, version 12.0; Advanced Chemistry Development Inc., Toronto, Canada). Kinetic aqueous solubility measurements were conducted on dry powder forms of particular examples that were being considered for further evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…40 Assessments of cytotoxicity were concurrently conducted on both human lung fibroblasts (MRC-5 cells; the host for T. cruzi) and primary peritoneal mouse macrophages (the host for L. inf), which revealed that the compounds were generally nontoxic (MRC-5 IC50s >55 µM except for 117: IC50 35 µM), as confirmed for TB (VERO assay 41 IC50s >128 µM for 71 of 72 compounds). Table 3) was not notable in comparison to the results for rac-4 (99% at 6.25 mg/kg), 11 suggesting that further optimisation of the side chain would be necessary. Indeed, while 28 showed good stability on exposure to mouse liver microsomes (MLM: 75% remaining after 1 h, Table 3) and gave a mouse pharmacokinetic (PK) profile comparable to rac-4 (Table 4 and Supporting Information, Figures S1 and S2), it was very hydrophobic (CLogP 5.14) and displayed poor solubility (~58 ng/mL at pH 7, Table 3; 62-fold lower than for rac-4 11 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Auckland medicinal chemistry group had synthesized multigram quantities of the racemate using a route shown in Scheme 1 that had been employed in initial work at the University of Auckland. 4 Pure enantiomers needed for preliminary efficacy and pharmacokinetic evaluation were prepared at the University of Auckland using a route similar to that shown in Scheme 2 below, but using 2-chloro-4-nitroimidazole in place of 2-bromo-4-nitroimidazole in step 3. This route was based on methods published by Otsuka Pharmaceuticals 5 for the synthesis of analogues of 2 .…”
Section: Antecedents and Resultsmentioning
confidence: 99%